Organizational Change Effect on Innovative Work Behaviour - Toksoy, Andaç; Çetin, Canan; Demiralay, Tülay (My University, 2017)
Today, change and innovation concepts have become the most important components for organizational success. In this context, this paper tries to explain the effects of innovative work behaviors of employees and managers on the organizational change. For this purpose, in a public university in Istanbul, 150 master degree students working have been questionnaired to collect data regarding with understanding the relation between variables. The data gathered has been analyzed using SPSS.

Günümüzde örgütlerin başarısı için değişim ve yenilik en önemli unsurlar haline gelmiştir. Bu bağlamda bu çalışmada, çalışanların ve yöneticilerin yenilikçi iş davranışının örgütsel değişim üzerindeki etkisi açıklanmaya çalışılmıştır. Bu amaçla İstanbul’da bulunan bir devlet üniversitesinde yüksek lisans yapan çalışan 150 kişiden elde edilen veriler değişkenler arasındaki ilişkiyi açıklamak için kullanılmıştır. Veriler SPSS programında analiz edilmiştir.
Örgütsel Değişimin Yenilikçi İş Davranışına Etkisi
Keywords: Organizational Change; Innovative work Behaviour; Structure Equation Model; Örgütsel Değişim; Yenilikçi İş Davranışı; Yapısal Eşitlik Modeli